PERANCANGAN MULTIMEDIA INTERAKTIF BIOLOGI SMA BERBASIS LITERASI SAINS DENGAN KONTEKS PADI - Siti Auliaddina (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2020)
Learning media have an important role in the teaching and learning process, because it makes the delivery of material in the learning process easier. One example of learning media is interactive multimedia based on scientific literacy. The main focus in the study of scientific literacy is the understanding of science which includes an understanding of nature through the mastery of basic science such as chemistry, biology and physics. So that interactive multimedia based on scientific literacy is very suitable in science learning. In this journal it was revealed about interactive learning media in the form of interactive videos of high school biology material based on the context of rice. In this journal the content of biology material from high schools is stated in the context of rice. The research methodology used is the waterfall method. Where after the authors analyze the content of High School Biology Material in accordance with the context of rice, then it is applied to the interactive multimedia created, and conduct interactive multimedia testing of high school students. After the usability test was conducted, the results were obtained that the interactive multimedia made could be well received and attracted the interest of most high school students who were correspondents.